The dark side of business flexibility. - Harrison, Bennett (Challenge (05775132))
Pressure on large corporations to cut their fixed costs and become more flexible in order to compete has had a severe effect on job security and worker remuneration. The stock market has instantly rewarded companies that cut costs through consolidations, mass layoffs, and wage and benefit rollbacks by increasing share values, which only further encourages this kind of management behavior. In addition, it seems that an increasing percentage of pay is becoming “contingent” on individual job performance, on the fortunes of the employer, on the current sentiments of the stock market, or on what the company believes it can get for its money by shifting to suppliers in lower-cost locations. These pressures have resulted in stagnating long-run average wages, falling personal mobility over time, and, possibly, increasing uncertainty regarding what a person's earnings will be in the future.